Perancangan Sistem Monitoring Kualitas Air (Suhu dan Salinitas) Lahan Budidaya Rumput Laut Menggunakan Mikrokontroler - Andi Rosman N; Abdul Zahir; Eka Sarwinda; Andi Wahyuni Suherman (Indonesian Journal of Fundamental Sciences, 2019)
The purpose of this research is to design a pond water quality monitoring tool using a microcontroller. The results showed that the temperature value at the location of the pond in the Palopo City fortress ranged from 24,339 0C to 26,044 0C for the first pond. While on the second pond, the temperature value ranges from 24,648 0C to 25,793 0C. For data on the condition of water salinity in the first and second ponds in the fortress area of Palopo, respectively are 500.72 ppm to 528.72 ppm and 536.39 ppm to 540.84 ppm. While data from the measurement of water quality in the rongkong river area shows that the temperature of the first pond is in the range of 27,011 0C to 27,835 0C. The temperature for the second pond is in the range of 26,418 0C to 27,392 0C. The condition of the first and second pond watersheds were 499.86 ppm to 524.60 ppm and 508.92 ppm to 536.16 ppm respectively.